Professional reflection as the factor of success of a sports coach - Zurida A. Sagova; Viktoriya M. Kapturova (Национальный психологический журнал, 2017)
Professional functions of modern trainers have long expanded from a simple function of training athletes to compete to the performance of the numerous roles of leader, organizer, psychologist, which are based on the ability of a coach to improve their professional skills and personal qualities.With the increasing popularity of sports, the means and conditions of sports training, the requirements to the quality of work and mastery of the main subjects of sports are increasing. The demand for a coach as a key figure in the education of successful athletes rises. The paper analyzes the research of criteria and factors of sports coach efficiency; the features of reflexive processes as one of the most effective ways of coach’s professional development. The correlation analysis performed in the work showed a significant connection between professional success and the reflexivity of trainers, which in general is correspondent with the results of similar studies performed in a number of other research fields. In the work there was no confirmation of the regular viewpoint inpsychological studies of the relationship between the success of activity and the personality’s internality, which induced a number of new assumptions about the nature of the interaction of successful coaches with their pupils, leadership style, and personality traits. The results of the study as a whole cause additional questions about individual psychological characteristics of respondents and allow to identify further research.